Practicality of Counseling Guidance Module Religious Based to Improve Academic Integrity - Karni, Asniti; Haryati, Asti (Kuras Institute, 2024)
The religiosity-based guidance and counseling module is an effort to overcome low academic integrity among students. In providing services, counselors are very dependent on textbooks available at school, and they have minimal other teaching materials. The research aims to determine the use of a religiosity-based counseling guidance module that is valid, practical, and effective. This study is quantitative research using the experimental research design. Product trials were carried out by 112 students of bengkulu city Public Junior High School, selected using the cluster random sampling technique. The data collection instruments are validation, practicality, and effectiveness instruments in the form of student response questionnaires. The research results showed that there was a significant difference between the pre-and post-test results in both the experimental group and control group trials. Where the average student score increased after using the religiosity-based counseling guidance module. Therefore, the results of this research can be said to be effective in presenting the results, namely 61.4 on the criteria of being quite effective, so that the module developed can improve students' academic integrity.